Cartel detection in procurement markets - Kai Hüschelrath; Tobias Veith (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Cartel detection is usually viewed as a key task of either competition authorities or compliance officials in firms with an elevated risk of cartelization. We argue that customers of hard core cartels can have both incentives and possibilities to detect such agreements on their own initiative through the use of market-specific data sets. We apply a unique data set of about 340,000 market transactions from 36 smaller and larger customers of German cement producers and show that a price screen would have allowed particularly larger customers to detect the upstream cement cartel before the competition authority. The results not only suggest that monitoring procurement markets through screening tools has the potential of substantial cost reductions - thereby improving the competitive position of the respective user firms - but also allow the conclusion that competition authorities should view customers of potentially cartelized industries as important allies in their endeavour to fight hard core cartels.
Keywords: D24; L41; L61; M11; M21; K21; 330; business economics; procurement; antitrust policy; cartels; detection; screening; Beschaffung; Kartell; Zementindustrie; Lieferanten-Kunden-Beziehung; Kontrolle; Deutschland